Optimization of chromium (VI) reduction in aqueous solution using magnetic Fe3O4 sludge resulting from electrocoagulation process. - Pınar Belibagli; Zelal Isik; Nadir Dizge; Deepanraj Balakrishnan; Abdul Rahman Afzal; Muhammad Akram (PLoS ONE)
The reuse of electro-coagulated sludge as an adsorbent for Cr(VI) ion reduction was investigated in this study. Electro-coagulated sludge was obtained during the removal of citric acid wastewater by the electrocoagulation process. The following parameters were optimized for Cr(VI) reduction: pH (5-7), initial Cr(VI) concentration (10-50 mg/L), contact time (10-45 min), and adsorbent dosage (0.5-1.5 g/L). Cr(VI) reduction optimization reduction experimental sets were designed using response surface design. Cr(VI) reduction optimization results 97.0% removal efficiency and 15.1 mg/g adsorption capacity were obtained at pH 5.0, 1.5 g/L electro-coagulated Fe3O4 sludge, 10 mg/L initial Cr(VI) concentration and 45 min reaction time. According to the isotherm results, the experimental data are compatible with the Freundlich isotherm model, and since it is defined by the pseudo-second order model emphasizes that the driving forces of the Cr(VI) reduction process are rapid transfer of Cr(VI) to the adsorbent surface. The reusability of the adsorbent was investigated and Cr(VI) reduction was achieved at a high rate even in the 5th cycle. All these results clearly show that electro-coagulated Fe3O4 sludge is an effective, inexpensive adsorbent for Cr(VI) removal from wastewater.